The Distributional Impacts of Worker Reallocation : Evidence from Europe - Bluedorn, John.; Caselli, Francesca; Hansen, Niels-Jakob.; Shibata, Ippei.. (Washington, D.C. : International Monetary Fund, 2022)
Using individual-level data for 30 European countries between 1983 and 2019, we document the extent and earning consequences of workers' reallocation across occupations and industries and how these outcomes vary with individual-level characteristics, namely (i) education, (ii) gender, and (iii) age. We find that while young workers are more likely to experience earnings gains with on-the-job sectoral and occupational switches, low-skilled workers' employment transitions are associated with an earnings loss. These differences in earnings gains and losses also mask a high degree of heterogeneity related to trends in routinization. We find that workers, particularly low-skilled and older workers during recessions, experience a severe earning penalty when switching occupations from non-routine to routine occupations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Fluctuations; Cycles; Job, Occupational, and Intergenerational Mobility; Labor Turnover; Promotion